Severe Hemolytic Anemia due to De novo Hemoglobin Sabine in an argentinian newborn: first case in South America - Perez, Susana (2015)
Hemoglobin (Hb) Sabine is an unstable Hb variant that causes hemolytic anemia in heterozygous state, with inclusion bodies in the red blood cells (RBC). This hemoglobin is the result of a point mutation at codon 91(CTG)(CCG) of the beta-globin gene. We report, for the first time in South America, the identification of Hb Sabine in a nine-month-old female baby, referred to our laboratory bearing a severe hemolytic anemia. We emphasize the need for the correct characterization of this unstable hemoglobin mainly for therapeutic purposes and for genetic counseling.